2010
DOI: 10.3177/jnsv.56.255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Blood Volume Fluctuation of Light Resistance Exercise after Ingestion of the High-Protein Snacks on Plasma Branched-Chain Amino Acid Concentrations in Young Adults

Abstract: SummaryThe study investigated exercise patterns resulting in the more efficient promotion of amino acid utilization. High-protein snacks (HPS; 15 g protein, 18 g sugar) were ingested by 8 young adult subjects 3 h after the basal meal ingestion. Sixty minutes after the HPS ingestion, the subjects performed arm flex/extend exercises for 15 min. The difference between 2 exercise patterns was compared. Pattern 1: High-number long-interval (HL) arm flex/extend (3 ϩ 3 s) exercise; the HL group performed 9 sets of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has been reported previously that ovalbumin and ovotransferrin from EWP fractions promote the growth of cultured muscle cells (C2C12 cells) ( 26 ) . In addition, the effects of the amino acids within EWP are likely because of the presence of branched amino acids in egg whites, which increase the branched amino acid concentrations in the blood when ingested ( 27 ) . After exercise, the concentrations of these amino acids decrease ( 27 ) , and it is possible that after exercise the branched amino acids in EWP are used for muscle repair and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported previously that ovalbumin and ovotransferrin from EWP fractions promote the growth of cultured muscle cells (C2C12 cells) ( 26 ) . In addition, the effects of the amino acids within EWP are likely because of the presence of branched amino acids in egg whites, which increase the branched amino acid concentrations in the blood when ingested ( 27 ) . After exercise, the concentrations of these amino acids decrease ( 27 ) , and it is possible that after exercise the branched amino acids in EWP are used for muscle repair and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of the amino acids within EWP are likely because of the presence of branched amino acids in egg whites, which increase the branched amino acid concentrations in the blood when ingested ( 27 ) . After exercise, the concentrations of these amino acids decrease ( 27 ) , and it is possible that after exercise the branched amino acids in EWP are used for muscle repair and hypertrophy. Consistent with this, the combination of strength training and EWP ingestion has been found to increase muscle mass and strength ( 28 ) , and egg whites are thus considered to be an effective source of protein for body building.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies on ingestion of proteins or amino acids prior to exercise have shown the ingestion to be effective in muscle protein synthesis (16)(17)(18). This study fixed the timing of HPS ingestion at 3 h after a basal meal (1)(2)(3)(4) in the SE and SS groups, thereby aiding the daily ingestion of proteins by elderly people with reduced appetite. Since the demands of the small intestine and liver are quickly met by amino acids from the protein of the basal meal, amino acids from the HPS protein are rapidly disseminated to the peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BCAAs have been reported to ameliorate muscle fatigue (Matsumoto et al., 2009). Their concentration in the blood increases after ingesting an EWP preparation and decreases after exercise (Kato, Numao, Miyauchi, & Suzuki, 2010). Therefore, an antifatigue effect mediated by BCAAs can also be expected.…”
Section: Introductionmentioning
confidence: 99%